C-reactive protein to albumin ratio is associated with increased risk of mortality in COVID-19 pneumonia patients - Gonca Koksaldı; Nurdan Unlu; Selen Acehan; Müge Gülen; Cem Isikber; Adem Kaya; Cagdas Ince; Basak Toptas Firat; Hilmi Erdem Sümbül; Salim Satar (Cukurova Medical Journal, 2021)
Purpose: The aim of this retrospective observational study is to compare C-reactive protein to albumin ratio and CURB-65 score in the emergency department in terms of predicting mortality in patients over the age of 18 who were hospitalized for COVID-19 pneumonia. Materials and Methods: The study includes 613 patients hospitalized between March 15 and April 30, 2020 due to COVID-19 pneumonia detected on thorax computed tomography at the emergency department pandemic area. Hospitalized patients were divided into groups according to positive and negative real-time polymerase chain reaction results. Results: While 73.1% (n: 448) of 613 patients included in the study were hospitalized in the ward, 26.9% (n: 165) were hospitalized in intensive care. 8.6% (n: 53) of the total patients died. In non-survivors patients the mean CURB 65 score was 4±1 (and C-Reactive Protein to Albumin Ratio was 5.6±4.2 Multivariate logistic regression analysis showed that CURB 65 and high C-Reactive Protein to Albumin Ratio are independent risk factors for COVID-19 pneumonia. Conclusion: The C-reactive protein to albumin ratio is as sensitive as CURB 65 and can guide the clinician in the early detection of patients with poor prognosis COVID-19 pneumonia.